Profil Pramuwisata Kawasan Geopark Ciletuh Palabuhanratu: Kompetensi dan Tantangannya dalam Menghadapi Era Tourism 4.0 - Ahmad Yani; Asep Mulyadi; Rosinta Rosinta (Jurnal Samudra Geografi, 2020)
The role of guides in a tourist area is significant because they are "ambassadors" for the state, management, and the local community. However, their existence is still not being noticed. In facing the Tourism 4.0 era, their challenges are getting more challenging because technology will displace them. They are threatened to become victims of disruption from these technological advances. The results showed that tour guides' qualifications and competence in the Ciletuh Palabuhanratu Geopark are still relatively low. This is due to the lack of attention from all parties. This research recommends that local governments, business actors related to tourism services (hotels, restaurants, banks, etc.) set aside their CSR to conduct training for guides through official organizations (HPI) in turns and are mutually beneficial.